キョクコウタイ ニ オケル ELF ホウシャ ノ トウライ ホウコウ カンソク - 佐藤, 夏雄; サトウ, ナツオ; 林, 幹治; ハヤシ, カンジ; SATO, Natsuo; HAYASHI, Kanji (国立極地研究所, 1976)
P(論文) The observation of arrival direction for elliptically polarized ELF and VLF electromagnetic waves, based on a new method developed by TSURUDA and HAYASHI (1975), was carried out at Syowa Station in Antarctica from March, 1974 to January, 1975. Some preliminary results are described concerning the arrival direction of daytime ELF emissions at the frequency of 0.75 kHz from December 24, 1974 to January 31, 1975. Statistically, the arrival direction depends on local time. The emission is mostly incident from north in the early morning, from south in the late morning, from south-west in the afternoon, and from north-west in the evening. In individual cases, it was often found that the arrival direction remained almost unchanged for several hours, or shifted gradually. The polarization of the emission is generally right-handed and is highly elliptical. departmental bulletin paper